FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN RAWAT INAP TERHADAP PELAYANAN DI RS MUHAMMADIYAH MEDAN TAHUN 2016 - HEPPY JELITA SARI BATUBARA (JURNAL ILMIAH KOHESI, 2019)
Background, This study aims to analyze the factors that affect the satisfaction of hospitalization in Muhammadiyah Hospital Medan of variables such as: Tangibels, Realibity, Responsiveness, Assurance, and Empaty, Variable above to see if the quality service is in accordance with the expectations of patients. The decline in the number of inpatients at MuhammadiyahMedan Hospital is thought to be related to patient satisfaction with the services provided. The method of this research is quantitative descriptive research using Cross Sectional design, where total population and sample are the same (total population) that is 35 patient. Data collection is done by using primary, secondary, and tertiary data. Data analysis was done by chi-square analysis with significant 0,05. The result showed that tangibles variables have correlation to patient satisfaction at inpatient wards of Muhammadiyah Hospital Medan at p value 0,005 (<0,05), Realibity variable have correlation to patient satisfaction at inpatient ward of Muhammadiyah Hospital Medan at p value equal to 0,001 (<0,05), Responsiveness variable has no correlation to patient satisfaction at inpatient ward of Muhammadiyah Hospital Medan at p value 1,000 (> 0,05), Assurance variable has no relation to patient satisfaction at inpatient ward of Muhammadiyah Hospital Medan at p value of 0,449 (> 0,05) and Emphaty variable have correlation to patient satisfaction at inpatient room of Muhammadiyah Hospital Medan at p value equal to 0,038 (<0,05). In conclusion, that variable of service quality (Tangibles, Realibity, and Emphaty) have relationship to patient satisfaction in inpatient room of Muhammadiyah Hospital Medan, while service quality variable (Responsivness and Assurance) have no relation to patient satisfaction at inpatient room of Muhammadiyah Hospital Medan, The authors suggest that the Muhammadiyah Hospital of Medan fixes all aspects of its service, not only the facilities but the system and human resources are important to be more pleasing to the patients who lead to the feeling of satisfaction.